Oxidative C−C bond cleavage of lignin via electrocatalysis - Huang, Jinshu; Jian, Yumei; Zhou, Min; Wu, Hongguo (Frontiers in Chemistry, 2022)
Lignin, which is an important component of biomass in nature and is constantly produced in industry, becomes potential raw material for sustainable production of fine chemicals and biofuels. Electrocatalysis has been extensively involved in the activation of simple molecules and cleavage-recasting of complex scaffolds in an elegant environment. As such, electrocatalytic cleavage of C−C(O) in β-O-4 model molecules of lignin to value-added chemicals has received much attention in recent years. This mini-review introduces various anodes (e.g., Pb, Pt, Ni, Co, and Ir) developed for electro-oxidative lignin degradation (EOLD) under mild conditions. Attention was placed to understand the conversion pathways and involved reaction mechanisms during EOLD, with emphasis on the product distribution caused by different electrodes.